2022
DOI: 10.1021/acscatal.2c04160
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Stabilizes Ceramic Titanium Oxynitride Support for Oxygen Evolution Reaction

Abstract: Decreasing iridium loading in the electrocatalyst presents a crucial challenge in the implementation of proton exchange membrane (PEM) electrolyzers. In this respect, fine dispersion of Ir on electrically conductive ceramic supports is a promising strategy. However, the supporting material needs to meet the demanding requirements such as structural stability and electrical conductivity under harsh oxygen evolution reaction (OER) conditions. Herein, nanotubular titanium oxynitride (TiON) is studied as a support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Note that carbon supports are extremely unstable as anode materials, especially in PEMWEs. Therefore, other alternatives with strong corrosion resistance, such as TiO 2 , Nb-doped TiO 2 (NTO), TiON, as well as Sb-, F-, or In-doped tin oxide (ATO, FTO or ITO) etc., have also been extensively deployed in acidic OER. ,, Metal/metal oxide support interactions (MMOSI), proposed by Strasser and co-workers, demonstrated that the interactions between oxide supports and IrO x nanoparticles were negligible in carbon-supported catalysts. (Figure a) .…”
Section: Iridium-based Acidic Oer Catalystsmentioning
confidence: 99%
“…Note that carbon supports are extremely unstable as anode materials, especially in PEMWEs. Therefore, other alternatives with strong corrosion resistance, such as TiO 2 , Nb-doped TiO 2 (NTO), TiON, as well as Sb-, F-, or In-doped tin oxide (ATO, FTO or ITO) etc., have also been extensively deployed in acidic OER. ,, Metal/metal oxide support interactions (MMOSI), proposed by Strasser and co-workers, demonstrated that the interactions between oxide supports and IrO x nanoparticles were negligible in carbon-supported catalysts. (Figure a) .…”
Section: Iridium-based Acidic Oer Catalystsmentioning
confidence: 99%
“…The TiO x N y –Ir catalyst was synthesized in a stepwise protocol as described in detail in our recent publication ( Figure 1 ). 19 Briefly, initially, the Ti TEM grid (3.05 mm diameter, 400 mesh, SPI Supplies) underwent potentiostatic anodization in a two-electrode cell using a stainless-steel counter electrode at a constant voltage of 40 V for 30 min, resulting in an amorphous TiO 2 nanotube film. For this purpose, a recently developed anodization apparatus was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, it enhances the conductivity of a support material derived from TiO 2 , primarily through the partial conversion of TiO 2 into TiN and the generation of Ti oxynitride (TiOxNy). 62 This concept revolves around the fact that TiN, despite its conductivity, undergoes gradual oxidation when exposed to OER conditions. Thermodynamically, transition metal oxides are more stable than their respective nitrides thus a passive transition metal oxide film is formed on the surface of the transition metal nitride when exposed to high voltage conditions, which act as a protective layer against corrosion.…”
Section: Metal Nitridesmentioning
confidence: 99%